Risks of zoonotic diseases from livestock and health literacy in Thiqar/Al rifai - Ali Mazahem Shanjar (University of Thi-Qar Journal of agricultural research, 2024)
The understanding, beliefs, and behaviors will be determined by this investigation regarding diseases that humans contract from animals. In this , 77 people functioning ( reproducers, obese animals, vendors) of cattle .wide open The Region of Al Rifai, ThiQar, Iraq. Those individuals addressed a sociodemographic inquiry notwithstanding one more three sorts of inquiries (information perspectives, methods), the information’s grade rating has been determined by emphasizing each question. Participants 72, they were 45 years old on average.. Approximately %87.6% of the participants had already recently contaminated, and %58.6 were unaware of this Just 12.6% of the participants got prepared about creature farming. %37.6 of the members used to have farming training 96% of the people that used to drink unsterilized milk of them will be aware that it can cause infections, and.%65 of aware of this. According to this research, the prevalence rate of attracting a disease from an animal was 5.6%. Gloves were worn by 36.2% of the participants, whereas veils were worn by only 28%. %13 did not use any private defensive hardware. The use of crude dairy was typical those that were unaware that it would be tainted (p =.) 0.02% The participants knew a great deal about the diseases that animals could transmit, but they were less aware that poultry could also be a source of contamination (P <0.001)..) Members don’t behave in an apparent defensive manner. the need for safety clothing or help getting ready, particularly when itcomes to using it.